Assessment of Temporomandibular Joint Disorders: Retrospective Study of Clinical Presentations - Aishla Jain; Samir Mansuri; Sonali Perti; Brajesh Gupta; Vaibhavi Raut; Sheetal Mujoo; Sunil K. Gulia (Wolters Kluwer Medknow Publications, 2024)
Objective: This retrospective research aimed to assess the clinical presentations and management strategies for "temporomandibular joint (TMJ)" disorders. Methods: Medical records of patients diagnosed with TMJ disorders between 2017 and 2022 were retrospectively analyzed. Data collected included demographic information, clinical symptoms, radiographic findings, treatment modalities, and treatment outcomes. Statistical analysis was performed to examine associations between variables and treatment outcomes. Results: A total of 150 patients were included in the research, with a mean age of 42.5 years. The most common presenting symptoms were pain (80.0%), limited mouth opening (60.0%), and clicking/popping sounds (40.0%). Muscle tenderness (53.3%) and jaw deviation (20.0%) were also observed. Treatment modalities encompassed pharmacotherapy, physical therapy, occlusal splints, and surgical interventions. Statistical analysis revealed significant associations between certain demographic characteristics and clinical presentations. Conclusion: This research provides valuable insights into the clinical presentations and management strategies for TMJ disorders. Pain, limited mouth opening, clicking/popping sounds, muscle tenderness, and jaw deviation were among the common symptoms observed. A multi-disciplinary approach involving various healthcare professionals is essential to optimize patient outcomes and improve quality of life for individuals affected by TMJ disorders.